Apoptosis and mutagenicity induction by a characterized aqueous extract of Baccharis articulata (Lam.) Pers. (Asteraceae) on normal cells - Cariddi, Laura Noelia (2012)
In a previous study we have demonstrated that cold aqueous extract of Baccharis articulata (Ba-CAE) induced the death of human peripheral blood mononuclear cells (PBMCs) and exerted low mutagenic effects on mice at 6 h after administration. The aim of this work was to investigate whether the PBMCsdeath induced by Ba-CAE is due to apoptosis, and whether this extract exerts mutagenic effects on mice at 24 and 48 h after administration. In addition, Ba-CAE was chemically characterized. PBMCs from healthy volunteers were exposed to extract (10, 20, 40, 80, 160, 320, 640 and 1280 lg/mL) for 18?24 h. Cell viability was determined by staining of trypan blue dye exclusion method. Apoptosis was determined by Hoechst 33258 staining, TUNEL, and DNA fragmentation analysis by agarose gel electrophoresis. BALB/c mice were injected with extract (1800, 900 and 450 mg/kg) and sacrificed at 24 and 48 h postinjection. Bone marrow samples were used to assess chromosome mutations by the micronucleus test. The extract induced PBMCs death by apoptosis and increased the frequency of micronuclei in bone marrow. The phytochemical study of Ba-CAE showed the presence of flavones as luteolin and acacetin, caffeoylquinic acids as chlorogenic acid, and tannins.